Evaluating the Implementation and Outcomes of a Community‐Based Doula Program in Washington State: A Mixed‐Methods Analysis. - Riley, Taylor; Buchanan, Zeruiah V.; Perera, Dila; Brickell, Kate Wilhite; Turrietta, Cynthia; Teal, Janae; Bess, Jami; Celis, Margarita; Egal, Hawa; Gladstone, Memorie; Hernandez, Betty; Prioleau, Vonda; et al. (Perspectives on Sexual & Reproductive Health, 2025)
Background: Community‐based doulas, who provide nonclinical perinatal support and are often from the same communities as the families they serve, are increasingly recognized as a strategy to ameliorate racialized perinatal health inequities. However, little is known about the successful implementation and sustainability of community‐based doula programs. Methods: Using an explanatory sequential mixed methods design, we examined the implementation and health outcomes of a community‐based doula program serving low‐income families and the barriers and facilitators that influence these outcomes. We analyzed programmatic and health outcome data among all families enrolled in the program from January 2016 through December 2022. Four in‐depth listening sessions with the program's direct service providers were conducted and analyzed using thematic analysis. Results: Among the over 1800 families served, the majority of whom identified as either Asian, Black, Indigenous, Latina/e/x, or multiracial, there were 14,672 total home visits that totaled 17,774 h. Over $87,000 in direct funds and 7000 tangible items (e.g., diapers) were dispersed to families. Preterm birth ranged from 4% to 9% across programs and most participants (> 94%) were breastfeeding/chestfeeding at birth. Direct service providers identified holistic, culturally‐matched services and "doula‐ing the doula" (organizational infrastructure to support doulas) as facilitators. Barriers included the intersecting systems of oppression that underlie the primary challenges faced by birthing families and direct service providers, including lack of community resources and power asymmetries within birth settings, that can lead to provider burnout. Conclusions: These findings document the positive impact of community‐based doula programs and bolster calls for increased compensation and structural supports for doulas.